Last-mile logistics: Analysis of retail sector in Lima Metropolitana during the COVID-19 pandemic - Castillo Loayza, Julia (2024)
This research analyzes Lima consumers' perceptions of last-mile logistics in their online retail purchases during the state of emergency caused by COVID-19. For this purpose, a mixed methodology was developed based on 134 surveys of consumers from different retail companies in the metropolitan area of Lima. In addition, in-depth interviews were conducted with experts in last-mile logistics, as well as with customers who made purchases during the pandemic period. The results of the hypotheses show that the current context has generated new online shopping habits in customers and evidence the emergence of new problems related to consumption and quality of service provided to the processes of online shopping and home delivery, with adequate sanitary logistics support.